Entomopathogenic fungi based microbial insecticides and their physiological and biochemical effects on Spodoptera frugiperda (J.E. Smith) - Vivekanandhan, Perumal; Swathy, Kannan; Lucy, Alford; Sarayut, Pittarate; Patcharin, Krutmuang (Frontiers in Cellular and Infection Microbiology, 2023)
‘The fall armyworm, Spodoptera frugiperda’, represents a significant threat to maize production, a major staple crop in Asian countries. In pursuit of more effective control of this insect pest, our study assessed the physiological and biochemical effects of the entomopathogenic fungus Metarhizium anisopliae against the larvae of S. frugiperda. Results revealed that, following nine days of treatment, a high concentration of conidia (1.5x107 conidia/mL-1) was toxic to all stages of larvae (second to fifth instar), resulting in 97% mortality of the second instar, 89% mortality of the third instar, 77% mortality of the fourth instar, and 72% mortality of fifth instar. All larval instars were found to have dose-dependent mortality effects. Treated S. frugiperda larvae further displayed significant physiological, morphological, and behavioral changes. Here, treated larvae displayed significantly lower levels of acetylcholinesterase, α-carboxylesterase, and β-carboxylesterase enzyme activity when compared to control groups. Treated larvae underwent an outward morphological change as the result of a decrease in the exterior cuticle of the anal papillae and a demelanization of the interior cuticle. Treated larvae also exhibited abnormal feeding behaviors as a consequence of the negative impact of conidia treatment on the neuromuscular system. Investigation into the effect of M. anisopliae on the non-target organism, the earthworm Eudrilus eugeniae, revealed that M. anisopliae conidia did not produce significant pathogenicity following three days of treatment. Furthermore, histological analysis revealed no significant effect of the entomopathogenic fungi on the gut tissue of the non-target organism. This study highlights the potential of M. anisopliae in the control of S. frugiperda.